3D structural modeling using seismic data and well logs for Khatatba reservoir in Matruh-Shushan Basin, North Western Desert, Egypt - Amr M. Eid; Walid M. Mabrouk; Mohammed Amer; Ahmed Metwally (Scientific Reports, 2023)
Abstract Middle Jurassic reservoirs present challenges in the northern segment of the Western Desert due to geometric uncertainties arising from structural configurations, lateral facies variations, diverse lithologies, and heterogeneous reservoir quality. Consequently, this study employed an intricate approach, constructing detailed 3D geostatic models by amalgamating diverse datasets, including 2D seismic sections and digital well-logs. The focus of these 3D models was on the Khatatba Formation (Upper-Safa Member, Kabrit Member, and Lower-Safa Member) in Matruh—Shushan Basin in the North Western Desert. The objectives encompassed assessing hydrocarbon potential, precisely estimating reserves, formulating development and exploration strategies, and identifying prospective drilling locations. The resultant structural model revealed a compartmentalized region marked by major and minor NE–SW trending normal faults, establishing structurally advantageous locations for hydrocarbon trapping within the study area. Petrophysical analyses highlighted the promising potential of the Upper-Safa Member as a reservoir, featuring porosity values ranging from 10 to 18%, peaking in the northeast sector, volume of shale (Vsh) between 15 and 24%, water saturation (Sw) spanning from 18 to 53%, and increased sand thickness towards the eastern section. Similarly, the Lower-Safa Member demonstrated favorable reservoir attributes, including porosity values ranging from 10 to 16%, with higher values in the southeastern part, Vsh between 17 and 28%, and Sw varying from 15 to 47%. The study findings underscored the hydrocarbon potential in the northeast block of the study area for the Middle Jurassic Khatatba Formation. These insights contribute valuable information for decision-making in exploration and production endeavors within the basin.